Livestock pricing in the northern Kenyan rangelands - Barrett, Christopher B.; Chabari, F.; Bailey, D.V.; Little, P.D.; Coppock, D. Layne (Oxford University Press, 2003)
This paper uses detailed, transactions-level data and an innovative, structural-heteroskedasticity-in-mean estimation method to identify the determinants of livestock producer prices for pastoralists in the drylands of northern Kenya. The empirical results confirm the importance of animal characteristics, periodic events that predictably shift local demand or supply and, especially, rainfall on the prices pastoralists receive for animals. Price risk premia are consistently negative in these livestock markets. The imposition of quarantines has a sharp negative effect on expected producer prices in the pastoral areas, revealing that Kenya's approach to animal disease control favours wealthier highlands ranchers and consumers at the expense of poorer drylands herders.